Production of recombinant norovirus VP1 protein and its antigenic and immunogenic properties - Vladislav A. Lapin; Dmitry V. Novikov; Ekaterina V. Mokhonova; Dmitry A. Melentyev; Maria I. Tsyganova; Dmitry E. Zaitsev; Viktor V. Novikov (Журнал микробиологии, эпидемиологии и иммунобиологии)
Introduction. The importance of noroviruses in human infectious pathology and the danger of large epidemic outbreaks in organized groups determine the need to develop means of specific prevention of infection.